THE ROLE OF SOME REGIONAL FACTORS IN THE ASSESSMENT OF WELL YIELDS FROM HARD-ROCK AQUIFERS OF FENNOSCANDIA - Henriksen H. (My University, 2003)
The attributes of about 13,600 hard-rock water wells were arranged in three profiles parallel to gradients of typical regional factors. These factors are thought to be of importance to groundwater yield from wells in the Fennoscandian crust and were subjected to a statistical analysis. The regional factors comprise annual rate of postglacial crustal uplift and annual average precipitation, whereas soil type, soil depth, and bedrock type are considered sub-regional and local factors. There is no clear trend in well yield along the regional gradients. The results of the statistical analysis indicate that for the typical regional variables, the rate of postglacial uplift and average annual precipitation explain not more than 11% of the observed variation in well yields. Some of these factors, and other factors not included in this study, work in opposite directions and may cancel each other out. It is concluded that other, more local factors, such as well depth, proximity to fracture-related lineaments and topography, have a greater influence on well yields in this area.
Keywords: CRYSTALLINE ROCKS; FENNOSCANDIA; GROUNDWATER FLOW; GROUNDWATER STATISTICS; GEOGRAPHIC INFORMATION SYSTEMS